Participatory F1 hybrid seed production of tomato and its economic benefit - KC, Ram B; Singh, Deepa; Lalchan, Chakra P; Joshi, Bal K (Journal of Agriculture and Environment, 2018)
Quality seeds play significant role in the agriculture production. This study was aimed to produce quality F1 seed of tomato by involving farmers at reasonable price and increase the availability of F1 hybrid ‘Srijana’ in commercial tomato growing areas of Nepal. The activities were carried out during three consecutive years from September 2009 to August 2012 in three sites i.e. Dhikurpokhari and Armala of Kaski district, and Mattikhan of Syangja district. Altogether 12 plastic houses were constructed for F1 seed production. Twelve female farmers and technicians from Agricultural Research Station (ARS), Malepatan; District Agricultural Development Offices from Kaski and Syangja districts and I/NGO personnel and seed entrepreneurs participated in different seed production activities. Parental lines of Srijana tomato hybrid were maintained in ARS, Malepatan. Training was provided to farmers on F1 hybrid seed production focusing on emasculation and pollination of tomato crop and crop protection. Farmers produced a total of 11.4 kg F1 seeds and able to get NRs 10,01,730 by selling their produce. The gross profit margin from production of F1 seed comprises 350 times more in comparison to maize seed production. The economic analysis showed that the net profit per kilogram of tomato F1 seed is 92%. F1 seed production has been carried out even by rural women farmers after getting good schooling of knowledge and skill through training. It indicates that F1 hybrid technology should be extended to other crops so that more farmers could get benefit from producing F1 hybrid seeds as well as by growing F1 hybrid crops.